Fabrication of Functional Nanofibers Through Post‐Nanoparticle Functionalization. Issue 7 (3rd March 2015) - Jeoung, Eunhee; Yeh, Yi‐Cheun; Nelson, Tyler; Kushida, Takashi; Wang, Li‐Sheng; Mout, Rubul; Li, Xiaoning; Saha, Krishnendu; Gupta, Akash; Tonga, Gülen Y.; Lannutti, John J.; Rotello, Vincent M.; et al.
<x xml:space="preserve">Abstract</x> A facile method is developed to functionalize nanofiber surfaces with nanoparticles (NPs) through dithiocarbamate chemistry. Gold nanoparticles (AuNPs) and quantum dots (QDs) are immobilized on the nanofiber surface. These surfaces provide scaffolds for further supramolecular functionalization, as demonstrated through the Förster resonance energy transfer (FRET) pairing of QD‐decorated fibers and fluorescent proteins. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>